Fading Charm of The Hijab in The Islamic Campus: A Perceptual Review of The Legacy-Negation of The Hijab at UIN Mataram - Muhammad Thohri; Ulyan Nasri (DINIKA : Academic Journal of Islamic Studies, 2026)
This study explores the evolving perceptions of hijab use in the Islamic campus environment, particularly at UIN Mataram, through a perceptual review of the legacy and negation of hijab among students. The study employs a mixed-method approach involving surveys and semi-structured interviews with 90 students to understand the factors influencing changes in hijab perceptions. The findings reveal a complex interaction between social, cultural, and religious dynamics, showing how gender roles, peer influence, and societal trends have contributed to the shifting views on hijab use. Additionally, the research highlights the divergence between female and male students’ perspectives on hijab, with a noticeable generational gap regarding its symbolic meaning. These results offer valuable insights for understanding the contemporary issues surrounding religious identity in higher education institutions, especially in the context of Islamic values and practices. The findings can inform policy-making and foster inclusive approaches to managing diversity in Islamic campuses.